The Role of the Current Account Balance in the Inflation Rate in Iraq in the Corona Pandemic: By using CoIntegration Methodology - Ahmed Hadi Salman (Genius Journals, 2022)
The Corona pandemic affected the Iraqi economy severely, leading to a serious deterioration in macroeconomic indicators, and the collapse of oil prices weakened the only financial resource in Iraq. Which deepened the imbalances in the structure of the public budget; the output and the (CURRT). Research importance: The dominance of oil exports makes the (CURRT) more vulnerable to damage in the Corona pandemic. Research problem: the rentier economy suffers from weak diversification of the structure of the (CURRT), which makes external shocks more effective in the local economic environment such as the Corona pandemic. Research hypothesis: The Corona pandemic causes more damage to the rentier economy, which leads to the disruption of economic activities. Research aims and methodology: Adopting Co-Integration technique to identify the effect of (CURRT) on (INF) in Iraq for the period (2005-2020), Research variables: (CURRT) to GDP ratio, official (EXCH), (INF). The research concluded that there is a co-integration relationship between the research variables and some causal relationships. The research recommended diversifying domestic production and then exports to strengthen the (CURRT) in the face of the Corona pandemic.
Keywords: Current Account Balance to GDP Ratio; Macroeconomic Indicators; Johansen Co-Integration Test; Engle-Granger Test